Is Policy Ownership An Operational Concept? - Boughton, James (IMF Working Papers; Working Paper ;, 2002)
IMF lending is generally conditional on specified policies and outcomes. These conditions usually are negotiated compromises between policies initially favored by the Fund and by the country's authorities. In some cases the authorities might be satisfied enough with the outcome to take responsibility for it ("own" it) even though it was not their original preference. In other cases, they might accept the outcome only to obtain financing, in which case weak commitment might lead to poor implementation. This paper reviews the theoretical basis for the importance of ownership, summarizes what is known about its empirical effects, and suggests a strategy for strengthening it.